The Analysis of English Abbreviation on Social Media “X” Used By Indonesian Artists - Fadila, Aulia Listi; Aziz, Yek Amin; Ariawan, Soni (Humanitatis : Journal of Language and Literature, 2025)
English abbreviations are widely used in digital communication, especially on platforms like X (formerly Twitter). Indonesian artists and influential public figures often use abbreviations in their posts, shaping language trends among their followers. This study aims to identify the types of English abbreviations used by Indonesian artists on X, as well as the contexts in which they are used. This research uses a qualitative descriptive method with a content analysis design, including thematic and linguistic analysis, to explore patterns and meanings in the use of English abbreviations on social media. This study collected data from 25 selected artists’ accounts from December 16, 2024, to January 16, 2025, to identify the types of abbreviations and their contexts of use. The results show that abbreviations are divided into four main categories: acronyms (40%), initials (34%), word shortening (20%), and word combinations (6%). In terms of usage, abbreviations appear most often in casual conversation (28%), followed by formal/professional communication (24%), promotion and marketing (20%), and memes or humor (28%). The findings show that acronyms are the most frequently used type of abbreviation, reflecting a preference for fast, efficient communication in X. In addition, this study highlights how social media shapes language habits and how the use of abbreviations can affect language learning. This study provides new insights into digital language trends and how online communication continues to evolve among artists and their followers.